2009
DOI: 10.1007/s12197-009-9090-6
|View full text |Cite
|
Sign up to set email alerts
|

The exchange traded funds’ pricing deviation: analysis and forecasts

Abstract: Exchange Traded Funds, Pricing Deviation, G10, G14,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 20 publications
3
36
6
Order By: Relevance
“…For Kotak Sensex ETF, 70% of variation in return is explained by index. This kind of behaviour is not surprising as ETFs are designed to track the designated benchmark (DeFusco et al, 2011) and the results are consistent with causality and cointegration results. It is only for Birla Sunlife Nifty ETF and Religare Invesco ETF that around 90% of the variation in return is explained by ETF.…”
Section: Stationarity Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…For Kotak Sensex ETF, 70% of variation in return is explained by index. This kind of behaviour is not surprising as ETFs are designed to track the designated benchmark (DeFusco et al, 2011) and the results are consistent with causality and cointegration results. It is only for Birla Sunlife Nifty ETF and Religare Invesco ETF that around 90% of the variation in return is explained by ETF.…”
Section: Stationarity Resultssupporting
confidence: 63%
“…Further, the discount and premium due to pricing deviation is attributable to volatility of index, momentum, illiquidity and size effect (Ackert and Tian, 2008). DeFusco et al (2011) observe that creation and redemption of ETFs (spider, diamonds and cube) leads to predictable pricing deviation that act as an additional implicit cost. The factors such as stationarity of the pricing deviation, clustering of volatility, lead-lag relationship, dividend accumulation and distribution explain such predictability in pricing deviation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, the deviations between price and NAV can be considered as short-run movements away from a long-run relationship. This mirrors the findings of Delcoure and Zhong (2007) for the 20 i-Shares, and Fujiwara (2006) andDe Fusco et al (2011) for the Spider fund. Similarly to the previous studies, the estimates of are close to unity, and this is confirmed statistically for the Satrix 40 and RESI funds, where the law of one price holds perfectly.…”
Section: Cointegration and The Law Of One Pricesupporting
confidence: 84%
“…De Fusco et al (2011) examined the price efficiency of the Spider, Diamond and Cube ETFs on the U.S. market. Similarly to Fujiwara (2006), they found that the Spider fund was price efficient based on the Engle-Granger test of cointegration, as was the Diamond fund.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Elia (2012) examines the premiums of Asian ETFs traded on the Italian markets, finding results comparable to Delcoure and Zhong (2007). DeFusco et al (2011) examine the pricing deviations of the three most liquid ETFs (Spider, Diamonds, and Cubes) between 1999 and 2007 and document a predictability of price deviations.…”
Section: Introductionmentioning
confidence: 97%